CD8+ PD-1+ T-cells and PD-L1+ circulating tumor cells in chemotherapy-naïve non-small cell lung cancer: towards their clinical relevance?. (June 2019) - Kotsakis, Athanasios; Kallergi, Galatea; Aggouraki, Despoina; Lyristi, Zaharoula; Koinis, Filippos; Lagoudaki, Eleni; Koutsopoulos, Anastasios; Georgoulias, Vassilis; Vetsika, Eleni-Kyriaki
Background: Since tumor cells may escape from immune surveillance through the programmed cell death 1 (PD-1)/programmed death ligand (PD-L)1 axis, this study was designed in order to evaluate whether there is a correlation between the levels of PD-1 + and PD-L1 + -expressing immune cells (ICs) and circulating tumor cells (CTCs) in patients with non-small cell lung cancer (NSCLC). Patients and methods: Peripheral blood was obtained from 37 chemotherapy-naïve patients with metastatic NSCLC before treatment. PD-1 and PD-L1 expression was evaluated (1) on ICs with anti-tumor function (CD4 + and CD8 + T-cells, B-cells, monocytes/dendritic cells) using flow cytometry, (2) on CTCs by immunofluorescence and (3) on cells from tumor tissues by immunohistochemistry. The levels of PD-1 + and PD-L1 + -expressing ICs were correlated with progression-free survival (PFS). Results: The presence of PD-1 + CD8 + cells, with reduced interferon (IFN)-γ expression, but not other ICs, were positively correlated with PD-L1 + CTCs ( p < 0.04). Increased percentages of PD-1 + CD8 + T-cells, were associated with a worse response to treatment ( p = 0.032) and shorter PFS ( p = 0.023) which, in multivariate analysis, was revealed as an independent predictor for decreased PFS [hazard ratio (HR): 4.1, p = 0.0007]. Conclusion: The results of the current study, for first time, provide evidence for a possible interaction between ICs and CTCs in NSCLC patients via the PD-1/PD-L1 axis and strongly support that the levels of PD-1 + CD8 + in these patients may be of clinical relevance.